Making sense of diverse data sources: reflections on an applied research project - Paris, Chris (Statistical and Social Inquiry Society of Ireland, 1995)
The aim of my paper today is to explore some of the tensions between 'practical' and theoretical issues involved in applied social analysis. I try to accomplish this aim by reflecting on an applied research project on demographic trends and housing need in Northern Ireland (Heenan, Gray and Paris, 1994). I do not simply summarise that project, however, but use it as the base from which to raise some wider issues which confront researchers and policy makers working in applied social research. The rest of this paper is in five parts. Section 2 introduces the applied research study and outlines some of its main results. Section 3 identifies the strategic housing policy context within which the research was undertaken. Section 4 focuses on some of the research issues involved in analysing demographic change. Section 5 explores the relationships between demographic analysis and public sector housing need assessment methodologies. My conclusions are set out in Section 6.
Read before the Society, 11 May 1995
Keywords: Research methodologies; Applied research projects; 314.15